The Reasons for School Dropout and Their Relationship To Some Variables - Shawbo Shamsaldeen Sulayman; Omar Hama Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The aims of the research is to find out the causes of school dropout and their relationship to some variables among a sample of pupils who dropped out for two years or more, and then joined the study in hasty schools. A random sample was selected by random stratified sample, the size of which was (291) students in the hasty schools. For the purpose of verifying the objectives of the research, a questionnaire consisting of (47) paragraphs was prepared, and the validity of the paragraphs of the questionnaire was verified by extracting the apparent validity, as well as the stability of the questionnaire was verified through two indicators, namely test re-test and the method of calculating the stability of the paragraphs by the method for each paragraph of the test For the purpose of analyzing the data, the chi-squared equation, the Cohen’s Kappa equation, the weighted mean equation, and the Kruskal-Wallis equation were used. The results were several reasons for school dropout related to the pupils, teacher, school administration, social and economic factors, and the cultural level of the family. At the end of the research, the researchers recommended several recommendations, and conducting several future researches as suggestions.